MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN PEMAHAMAN GURU DALAM MENGGUNAKAN TEKNOLOGI MODERN DI MTS NURUL IKHWAN TANJUNG MORAWA - Neliwati; Muhammad Abdullah Syarif; Khairul Fikri Sikumbang; Rahmat Nur Utama (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the management of the madrasah principal in improving teachers’ understanding of the use of modern technology at MTs Nurul Ikhwan Tanjung Morawa, identify the obstacles encountered, and describe the efforts undertaken by the principal to overcome these challenges. This research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, with the principal and teachers of MTs Nurul Ikhwan Tanjung Morawa as the research subjects. The findings indicate that the principal has implemented management functions consisting of planning, organizing, implementing, and supervising in enhancing teachers’ understanding of modern technology utilization. The obstacles faced include differences in teachers’ levels of digital literacy, limited facilities and infrastructure, and teachers’ limited time to participate in training programs. The efforts made by the principal include conducting training and professional development for teachers, academic supervision, mentoring in the use of technology for teaching and learning, and providing supporting facilities. This study concludes that effective madrasah principal management plays a significant role in improving teachers’ understanding of modern technology and contributes to the enhancement of learning quality in the madrasah.